AKTIVITAS ANTIINFLAMASI DAN ANTIOKSIDAN KOMBINASI EKSTRAK ETANOL BUNGA ROSELA (Hibiscus sabdariffa) DAN DAUN PEGAGAN (Centella asiatica) PADA TIKUS WISTAR JANTAN DENGAN OBESITAS - Kaniawati, Marita; Sulaeman, Agus; Susilawati, Elis; Zinan, Daula Zahra; Irviansyah, Cepy Okta (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
One of the triggers for obesity is high fat and high carbohydrates foods which increase Free Fatty Acid (FFA) and Reactive Oxygen Species (ROS), that trigger oxidative stress and chronic inflammation, which play a role in various degenerative diseases. This study aims to determine the potency and effective dose of ethanol extract of roselle flowers (Hibiscus sabdariffa) and gotu kola leaves (Centella asiatica) combination on oxidative stress (represented by Malondialdehyde or MDA) and its effect on inflammation (represented by Tumor Necrosis Factor-α or TNF-α). This research used in vivo experimental preventive method using 35 mice which were divided into normal group, induction group, comparison group curcumin 1.8 mg/kgBW, test group 1 EDP 200 mg/kgBW, test group 2 EBR 250 mg/kgBW, test group 3 EBRDP 125:200 mg/kgBW and test group 4 EBRDP 250:100 mg/kgBW. MDA levels were measured using UV-Vis spectrophotometry at 532 nm and TNF-α levels were measured using an ELISA kit on the 60th day. The results showed a decrease in blood MDA levels in EDP 200 mg/kgBW, EBR 250 mg/kgBW and EBRDP 250: 100 mg/kgBW and in liver MDA levels in EDP 200 mg/kgBW and EBRDP 250:100 mg/kgBW. The study also showed decreasing TNF-α levels in EDP 200 mg/kg BW, EBR 250 mg/kgBW, and the combination of EBRDP dose 125:200 mg/kgBW. In conclusion, the combination of EBRDP dose 250:100 mg/kgBW is the most effective dose in reducing MDA levels. The combination of EBRDP dose 125:200 mg/kgBW is the most effective dose in suppressing TNF-α levels.